2019
DOI: 10.18632/aging.102292
|View full text |Cite
|
Sign up to set email alerts
|

ACADS acts as a potential methylation biomarker associated with the proliferation and metastasis of hepatocellular carcinomas

Abstract: Background: Hepatocellular carcinomas (HCC) constantly rank among the malignancies with the highest death tolls on the global scale. Moreover, HCC are associated with a limited set of therapeutic options. This is particularly true in the case of advanced stage cancers, where long-term survival is uncommon. For the inoperable, advanced HCC patients, chemotherapy is the main modality of treatment. Due to the lack of known molecular targets, the efficacy of the chemotherapy is limited.Conclusion: These findings c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Cancer develops through the accumulation of genetic and epigenetic aberrations, and epigenetic changes are strongly associated with the development of HCC. As reported, many genes such as ADRAIA, ACADS, UBE2Q1, and ZCCH13 have been found to have aberrant methylation status in HCC (Hu et al 2017;Chen et al 2019;Li et al 2019;Chen et al 2020). Abnormal methylation of genes may be promising biomarkers to timely and accurately distinguish patients with HBV-associated HCC from patients with CHB.…”
Section: Discussionmentioning
confidence: 84%
“…Cancer develops through the accumulation of genetic and epigenetic aberrations, and epigenetic changes are strongly associated with the development of HCC. As reported, many genes such as ADRAIA, ACADS, UBE2Q1, and ZCCH13 have been found to have aberrant methylation status in HCC (Hu et al 2017;Chen et al 2019;Li et al 2019;Chen et al 2020). Abnormal methylation of genes may be promising biomarkers to timely and accurately distinguish patients with HBV-associated HCC from patients with CHB.…”
Section: Discussionmentioning
confidence: 84%
“…ACADS is a key short variant of the acyl-CoA dehydrogenase (ACAD) gene family and might be a methylation biomarker in HCC. The expression level of ACADS was negatively correlated with the DNA methylation level [ 25 ]. However, as a key metabolic enzyme, the role of ACADS in fatty acid metabolism in patients with HCC is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that DNA methylation plays a key role in regulating ACADS which made it a potential therapeutic target for treating HCC. 37 HSD17B13 is a kind of genetic variants in retinol metabolism, which is associated with liver injury progression. 38 Lu et al found that HSD17B13 was a tumor suppressive gene that inhibits HCC cell glycolysis as revealed by glucose utilization, lactate production, and extracellular acidification ratio.…”
Section: Discussionmentioning
confidence: 99%